Universidade e Sociedade na Amazônia Contemporânea: análise do processo de interiorização do ensino superior público na região amazônica - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This study aims at the process of expansion of the Brazilian public university for the countryside of the municipalities in the states of the brazilian Amazon occurred along the last decades. Its objective is to unravel some of their main determinants, especially those immediately derived of the material mode of production of the contemporary sociability. For this, from the ontological and epistemological suppositions extracted of the Marxist conception, realizes bibliographical consultation and the wide literature, of distinct areas in the Human Sciences. Revered for this bibliographical material, it approaches, first, the emergence and the development of the university in the world and in Brazil, seeking to handle some essential determinations of both processes. The analyses undertaken of the development of the university in the universality and in the particularity of the Brazilian situationtreats then, on the condition of the solid singular manifestation of those wider development, of the expansion of the Brazilian public university by the Amazon countryside,searching to identify some specific determinants that besides of universal determinants and particular, gave cause to this expansion
Keywords: Universidade - Amazônia; Capitalismo; Neoliberalismo; University - Amazônia; Capitalism; Neoliberalism; CIÊNCIAS HUMANAS; CIÊNCIAS HUMANAS: EDUCAÇÃO